DNA containing CpG motifs induces angiogenesis - Zheng, Mei (National Academy of Sciences, 2002)
New blood vessel formation in the cornea is an essential step in the pathogenesis of a blinding immunoinflammatory reaction caused by ocular infection with herpes simplex virus (HSV). By using a murine corneal micropocket assay, we found that HSV DNA (which contains a significant excess of potentially bioactive “CpG” motifs when compared with mammalian DNA) induces angiogenesis. Moreover, synthetic oligodeoxynucleotides containing CpG motifs attract inflammatory cells and stimulate the release of vascular endothelial growth factor (VEGF), which in turn triggers new blood vessel formation. In vitro, CpG DNA induces the J774A.1 murine macrophage cell line to produce VEGF. In vivo CpG-induced angiogenesis was blocked by the administration of anti-mVEGF Ab or the inclusion of “neutralizing” oligodeoxynucleotides that specifically oppose the stimulatory activity of CpG DNA. These findings establish that DNA containing bioactive CpG motifs induces angiogenesis, and suggest that CpG motifs in HSV DNA may contribute to the blinding lesions of stromal keratitis.